Characterization and Expression Profiles of Juvenile Hormone Epoxide Hydrolase From Lymantria dispar (Lepidoptera: Lymantridae) and RNA Interference by Ingestion. Issue 1 (8th February 2018) - Wen, Rongrong; Wang, Buyong; Wang, Bowen; Ma, Ling
Abstract: Juvenile hormone epoxide hydrolase (JHEH) is an important enzyme in the degradation pathways of juvenile hormone (JH) in insects. It converts JH to JH diol and hydrolyses JH acid to JH acid diol. JHEH titers regulate the entire process of insect development. In this study, full length ldjheh cDNA (2101 bp) was cloned from the Asian gypsy moth Lymantria dispar (L.; Lepidoptera: Lymantridae), and provisionally designated ldjheh1 . LdJHEH1 was characterized by predicted molecular weight of 52.64 kDa, theoretical isoelectric points of 6.87 and contains a transmembrane domain at the N-terminus. The transcriptional profiles of ldjheh1 were detected by qRT-PCR. The ldjheh1 was found to be expressed throughout all developmental stages with maximum expression levels occurring in fourth instar larvae. The ldjheh1 mRNA was detected in the heads, thoraces, and abdomens of gypsy moth larvae on day 2 of the third instar. The ldjheh1 was also detected in bodies of third instar larvae stage, with the highest peaks occurring at 24 h after ecdysis. The ldjheh1 gene was successfully knocked down by oral delivery dsRNA in the third instar larvae of L. dispar . The dsRNA targeting ldjheh1 was produced in vitro. Ingesting dsRNA for ldjheh1 only slightly delayed larval development.